Catch of currant pests (Lamporna capitella, Euhyponomeutoides albithoracellus and Synanthedon tipuliformis) in pheromone traps in Sweden, Norway and Finland 2021-2023 - Svensson, Glenn; Anderbrant, Olle (Lund University, 2025)
Data describe catches of male moths in traps baited with species-specific sex pheromones. Three species of black currant pests in Sweden, Norway and Finland were investigated: Lamporna capitella, Euhyponomeutoides albithoracellus and Synanthedon tipuliformis. Data show total weekly catches of males in four traps per field. NA indicates weeks when traps were not listed and checked.

Data beskriver fångster av fjärilshanar i klisterfällor betade med artspecifika sexualferomoner. Tre arter av skadegörare i svart vinbärsodling i Sverige, Norge och Finland analyserades: Lamporna capitella, Euhyponomeutoides albithoracellus och Synanthedon tipuliformis. Data redovisar den totala veckovisa fångsten av hanar i fyra fällor per fält. NA indikerar veckor då fällorna inte besöktes och fångsten inte analyserades.
Fångst av skadegörande insekter på vinbär (Lamporna capitella, Euhyponomeutoides albithoracellus och Synanthedon tipuliformis) i feromonfällor i Sverige, Norge och Finland 2021-2023
Keywords: Species distribution; Arters utbredning; methods of pest control; bekämpningsmetoder; insect pests; skadeinsekter; Euhyponomeutoides albithoracellus; mindre vinbärsbrunmal; Ribes nigrum; svarta vinbär; Synanthedon tipuliformis; vinbärsglasvinge; Lampronia capitella; vinbärsknoppmal; Ecology; Ekologi; Biota; Biologi och ekologi